Teaching and assessing EIL in local contexts around the world - Mckay, Sandra; Brown, James Dean (New York : Routledge, 2016)
English today is both a global language and at the same time embedded in a great variety of social contexts, resulting in linguistic and pedagogical variation. Taking a new look at the teaching and assessing of English as an international language (EIL), this text highlights overarching principles and provides specific strategies for responding to questions and challenges posed by the changing demographics of English language learners and users around the world. Teaching and Assessment in EIL Classrooms introduces an original, coherent framework in which needs analysis, pedagogical principles..
Discussion QuestionsApplication Tasks; EIL Teaching/Learning Principles; Index.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Foreign speakers; Communication, International; Electronic books